2022
DOI: 10.1186/s12969-022-00765-9
|View full text |Cite|
|
Sign up to set email alerts
|

The risk of depression and anxiety is not increased in individuals with juvenile idiopathic arthritis – results from the south-Swedish juvenile idiopathic arthritis cohort

Abstract: Background Children with chronic diseases are reported to have increased risk of psychiatric comorbidity. Few studies have investigated this risk in juvenile idiopathic arthritis (JIA), with conflicting results. We performed a population-based, longitudinal cohort study of the risk of depression and anxiety in south-Swedish patients with juvenile arthritis. Methods The south-Swedish JIA cohort (n = 640), a population-based cohort with validated JIA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Consistent with trends in the general population [ 42 ] and those previously reported in JIA [ 14 , 18 , 41 , 54 ], our results showed that females were more likely to have conspicuous screening results and higher symptom severity than males. Moreover, we have shown that the risk for conspicuous depressive and anxiety symptoms increases significantly with age, with older patients more frequently reporting higher symptom severity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with trends in the general population [ 42 ] and those previously reported in JIA [ 14 , 18 , 41 , 54 ], our results showed that females were more likely to have conspicuous screening results and higher symptom severity than males. Moreover, we have shown that the risk for conspicuous depressive and anxiety symptoms increases significantly with age, with older patients more frequently reporting higher symptom severity.…”
Section: Discussionsupporting
confidence: 92%
“…Few previous studies on internalizing symptoms in JIA have highlighted an increased risk in specific outcomes such as depression and anxiety compared to the general population [ 9 , 39 – 41 ]. Methodological discrepancies, but also sometimes small heterogeneous samples, differences in disease durations/activities, and the high rate of mental health problems in the general population may explain why some previous studies have stated no increased risk of mental health problems in JIA patients compared to general population controls [ 13 , 15 18 , 43 ]. As our study did not include a control group, an exact comparison with the general population is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this finding may be subject to type 1 error given the overall low enthesitis count (median was zero) in the small cohort, it is supported by other studies that have shown patients with enthesitis have higher pain, worse function, and worse quality of life. 14 The study therefore adds to the mixed evidence in the literature of the relationship between depression/anxiety symptoms and JIA disease metrics, 9,14 finding inconsistent associations with disease activity, physical function, and disability. Given the potential for subjectivity even in physician-reported disease measures, inclusion of more specific and objective markers of disease inflammation may be helpful in future studies.…”
mentioning
confidence: 83%
“…8 In contrast, another longitudinal study of a Swedish JIA cohort (N = 640) found that the incidence of depression and anxiety in JIA were not statistically different than in healthy controls. 9 It is worth noting, however, that even if rates of mental health problems in JIA are similar to peers on a group level, mounting evidence points to the need to address these problems for affected JIA youth to optimize overall health and outcomes. 5,10 The study findings also highlight the importance of identifying and addressing anxiety, particularly in youth with JIA.…”
mentioning
confidence: 99%